Action! : interviews with directors from classical Hollywood to contemporary Iran - Morris, Gary, 1951- (Anthem Press, 2009)
'Action!' draws on the very best published and unpublished interviews of the 'Bright Lights Film Journal', and contains many gems, including the last ever interview given by Francois Truffaut, four months before he died.
Keywords: Motion picture producers and directors -- Interviews.; Motion pictures -- Production and direction.; Producteurs et réalisateurs de cinéma -- Entretiens.; Cinéma -- Production et réalisation.; PERFORMING ARTS -- Film & Video -- Reference.; ART -- Film & Video.; PERFORMING ARTS -- Film & Video -- Direction & Production.; Motion picture producers and directors; Motion pictures -- Production and direction; Filmregisseur; Film; Interviews